2017
DOI: 10.1371/journal.pone.0181091
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the cAMP-dependent protein kinase (PKA) catalytic subunit isoforms

Abstract: The 3’,5’-cyclic adenosine monophosphate (cAMP)-dependent protein kinase, or protein kinase A (PKA), pathway is one of the most versatile and best studied signaling pathways in eukaryotic cells. The two paralogous PKA catalytic subunits Cα and Cβ, encoded by the genes PRKACA and PRKACB, respectively, are among the best understood model kinases in signal transduction research. In this work, we explore and elucidate the evolution of the alternative 5’ exons and the splicing pattern giving rise to the numerous PK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 67 publications
0
42
0
1
Order By: Relevance
“…The oncogenic J-PKAcα has been crystallized here for the first time in one of its most important physiological states where it is associated in a holoenzyme complex with the RIα subunit. This structure demonstrates that the N-terminal fusion does not interfere with the general organization of the R 2 :PKAcα 2 holoenzyme, and this also has relevance for the various PKAcα isoforms some of which have large extensions at the N-terminus (Søberg et al, 2017). Comparing the conformational states of the wt and chimeric RIα holoenzymes that display some novel interfaces may guide the development of drugs that selectively target not only to the J-domain and catalytic core to directly block chimera activity, but also regions present only at the holoenzyme level to block holoenzyme activation.…”
Section: Discussionmentioning
confidence: 83%
“…The oncogenic J-PKAcα has been crystallized here for the first time in one of its most important physiological states where it is associated in a holoenzyme complex with the RIα subunit. This structure demonstrates that the N-terminal fusion does not interfere with the general organization of the R 2 :PKAcα 2 holoenzyme, and this also has relevance for the various PKAcα isoforms some of which have large extensions at the N-terminus (Søberg et al, 2017). Comparing the conformational states of the wt and chimeric RIα holoenzymes that display some novel interfaces may guide the development of drugs that selectively target not only to the J-domain and catalytic core to directly block chimera activity, but also regions present only at the holoenzyme level to block holoenzyme activation.…”
Section: Discussionmentioning
confidence: 83%
“…of the sperm form of the enzyme with the somatic form of the PKA catalytic subunit would sustain normal sperm function is not known. However, it is intriguing that exon 1b, the sperm specific isoform of PKA, is present only in mammals (Soberg et al, 2017). Non-mammalian species only contain the isoform derived from utilization of exon 1a ( Figure 4B).…”
Section: The Proteins Pp1γ2 Gsk3α Pka Cα2 and Ppp3r2/cc Present Onmentioning
confidence: 99%
“…Recently we performed alignments of exon 1-1 encoded Cα1/Cβ1 across species after the gene duplication yielding Cα and Cβ isoforms, and pre-duplication catalytic subunit [designated C1, ( 188 )] residues reveals several conserved features in the N-terminus during evolution of the C subunit. Out of all 15 positions, position 1 and 2 is invariably Gly1 and Asn2 in both Cα1 and Cβ1, as well as C1, an ancient form of Cα and Cβ.…”
Section: Structural Relationships Of the N-terminal End Of The C Subumentioning
confidence: 99%
“…It is well-established that Gly1 may have a function in mammals through its modification of myristoylation by the enzyme NMT ( 74 ). We have suggested that N-myristoylation of PKA C subunits is a feature found in all vertebrate Cα1/Cβ1 subunits, and maybe even all metazoan C1 subunits in general ( 188 ). N-terminal myristoylation of proteins appears to be an ancient mechanism, with the common ancestor gene of NMT possibly arising in early eukaryotic cells ( 189 ).…”
Section: Structural Relationships Of the N-terminal End Of The C Subumentioning
confidence: 99%
See 1 more Smart Citation